Innovative Education? A Test of Specialist Mimicry or Generalist Assimilation in Trends in Charter School Specialization Over Time. (January 2015) - Renzulli, Linda A.; Barr, Ashley B.; Paino, Maria
By most media accounts, charter schools are innovative schools. But little empirical work interrogates this idea. We examine the growth and decline of specialist charter school mission statements as one indicator of innovation. In line with theories of resource partitioning, we find that specialist charter school missions—those asserting innovation with regards to populations served, curricula utilized, and/or educational focus—have become increasingly diverse over time. However, simultaneously, we find support for a generalist assimilation hypothesis: Charter schools have come to resemble traditional schools through isomorphic tendencies over time. Hence, we show that although specialist charter schools are becoming increasingly diverse in their missions, these charter schools are increasingly making up a smaller portion of the population. We also find, counter to charter school advocates' intentions, that states with more permissive charter school laws are those that also tend to have a great proportion of charter schools with generalist missions. Our findings contribute to a theoretical understanding of specialist organizations by considering specialization as an example of innovation in the charter school population. Furthermore, our findings have implications for the way charter school laws are created and enacted to foster innovation through specialization.